Penerapan Prinsip Good Governance Dalam Pengelolaan Anggaran Pendapatan Dan Belanja Desa (APBDes) Di Desa Sarireja Kecamatan Tanjung Kabupaten Brebes - Rita Isnaeni; Maftukhin Maftukhin; Titi Rahmawati (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This study aims to determine: the effect of partial and simultaneous accountability and transparency on the management of APBDes. This type of research is quantitative. The population of this research is village officials, members, VCB (Village Consultative Body) and community leaders using a sample of 50 respondents. Data collection method by distributing questionnaires to respondents directly. The technique of determining the number of samples in the study used a random sampling technique. The analysis used is multiple linear regression analysis using the SPSS 25 program. The results of the study stated that: 1) accountability had a partial effect on the management of the APBDes with a contribution of 43.4%. 2) transparency has no partial effect on the management of the APBDes. 3) accountability and transparency simultaneously affect the management of APBDes with a contribution of 56.6%. APBDes management can be explained by the variation of the two independent variables of 43.4%. More attention is needed from the government of Sarireja Village, Tanjung Subdistrict so that the management of the APBDes can be more accountable and transparent.